Dirāsah ‘an Al-Ibdāl fī ‘Ilmi Al-Sharfi - Aflisia, Noza; Rini, Rini; Yul, Widiya (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
Abtract Grammar plays a very important role in Arabic. It will help learners understand Arabic well and make others understand what we say. One of the Arab rules is Al-Ibdal. Many learners find it difficult to recognize the changing words because they do not know the origin of the changing letters. It is not only found in the Quran but also in Balaghah, Sharaf and other Arabic sciences. This research discusses Al-Ibdal, its language and terminology definitions, its letters, its benefits, its rules, and its divisions. This research is a Library Research, and data sources were derived from different books and journals. Then an understanding and analysis of these sources were carried out. The result is that Al-Ibdal is to create a character in place of a character while retaining the rest of the word characters. It has nine characters. One of the benefits of Al-Ibdal is that it avoids the wrong literature in understanding literary texts. It has many rules in general divided into ibdal sharfi or ibdal mutharrad and ibdal lughawi or ibdal ghairu mutharrad. Keywords : Ibdal, Arabic, Sharaf, Isytiqaq